A Manuscript of Masnavi Ramzul Ishq - Rafaqat Ali Shahid (بازیافت)
Masnavi Ramzul Ish'q is a unique literary master piece of Classic Urdu Literature. It also has great importance as an early Urdu writing in Punjab. It is an important Urdu poetic composition on mysticism. Masnavi Ramzul Ish'q was written by Ghulam Qadir Shah, a famous Noshahi Sufi (mystic leader) of Punjab. Masnavi Ramzul Ish'q is famous among mystic lovers and in Urdu literary circles, so several manuscripts of this Masnavi have been prepared by various scribers and have been found so far. Some of them are considered important in the editing and studying of this  Masnavi. This article deals with another and an unfamiliar copy of the manuscript of Masnavi Ramzul Ish'q. In this article, the writer provides essential and important information about the concerned manuscript. He has covered various aspects of the detailed study of this manuscript.